2016
DOI: 10.5114/bta.2016.64543
|View full text |Cite
|
Sign up to set email alerts
|

Callus induction and plant regeneration of Valeriana officinalis are affected by different leaf explants and various concentrations of plant growth regulators

Abstract: Valeriana officinalis, commonly known as valerian, is native to Europe and Asia and has economic importance as a medicinal plant. The effects of auxins (2,4-D and NAA) on callus induction were studied in vitro using basal piece of leaf + petiole (L1) and middle piece of leaf (L2) ). The results revealed that the effect of explant type on callogenesis was also significant. In contrast to KIN or TDZ, addition of IBA to BAP showed positive synergistic effect for plant regeneration and shoot number per callus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…Regarding shoot emergence, the results revealed that lower concentrations of both 6-benzyl amino purine (BAP) and α-naphthalene acetic acid (NAA) significantly have positive effect on shoot emergence (Table 1). These findings are in consistent with the results of Zamini et al [10] who reported that the excellent regeneration (82.5%), shoot length (5.96 cm) and shoot number (5.87) of Valeriana officinalis was resulted at lower level of BAP 0.5 mg/L along with IBA 0.5 mg/L. Excellent shoot regeneration percentage (60.00%) was also reported by Zebarjadi et al [14] with 0.5 mg/L NAA + 2 mg/L BAP in Valeriana officinalis.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Regarding shoot emergence, the results revealed that lower concentrations of both 6-benzyl amino purine (BAP) and α-naphthalene acetic acid (NAA) significantly have positive effect on shoot emergence (Table 1). These findings are in consistent with the results of Zamini et al [10] who reported that the excellent regeneration (82.5%), shoot length (5.96 cm) and shoot number (5.87) of Valeriana officinalis was resulted at lower level of BAP 0.5 mg/L along with IBA 0.5 mg/L. Excellent shoot regeneration percentage (60.00%) was also reported by Zebarjadi et al [14] with 0.5 mg/L NAA + 2 mg/L BAP in Valeriana officinalis.…”
Section: Discussionsupporting
confidence: 94%
“…Zamini et al [10] organized a method for callus initiation of Valeriana officinalis by using NAA and 2,4-D. Excellent induction of callus (95.83%) resulted with KIN 1 mg/L along with 2,4-D 1.5 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…Calli fresh and dry weights (g/jar). Data tabulated in Table (1) clearly show that calli fresh and dry weights of leaf, stem, and root explants of Valerina officinalis L. Data showed significant differences between the varied medium of different growth regulators concentrations, explants compared to the control medium. The tested leaf, stem, and root explants cultured on MS+5 ppm BA; MS+5 ppm D; MS+5ppm BA+3ppm The same letters in each column mean non-significant difference; Each value is the average of 3 replicates.…”
Section: Standards Authentic Preparationmentioning
confidence: 95%
“…The Valeriana genus is a member of the Valerianaceae family, and has 419 species. Valeriana officinalis L. (Valerian), is indigenous to Europe and Asia and widely distributed in Chile, Brazil, South Africa, the United States, and subtropical Asia, and is regarded as the most commercially significant species [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation